Developing Moral Reason Through Personal Guidance - Palasara Brahmani Laras; Juntika Nurihsan; Mamat Supriatna (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2019)
The study aims to know the effectiveness of personal guidance to develop moral reasoning. This research method used a quasi-experimental with a non-equivalent pretest-posttest control group design. Data collection used a moral reasoning questionnaire covering aspects of compliance, truth, and justice. The research sample consisted of 66 students of class VIII SMP N 2 Ciledug. The sampling technique used purposive sampling. The results showed that personal guidance was effective in developing students' moral reasoning. The benefits of the results of this study can be used as a basis for consideration in developing guidance and counseling service programs, especially in developing personal guidance services in improving adolescent moral reasoning.